Progress update from the hippocampal subfields group. Issue 1 (13th June 2019) - Olsen, Rosanna K.; Carr, Valerie A.; Daugherty, Ana M.; La Joie, Renaud; Amaral, Robert S.C.; Amunts, Katrin; Augustinack, Jean C.; Bakker, Arnold; Bender, Andrew R.; Berron, David; Boccardi, Marina; Bocchetta, Martina; et al.
Abstract: Introduction: Heterogeneity of segmentation protocols for medial temporal lobe regions and hippocampal subfields on in vivo magnetic resonance imaging hinders the ability to integrate findings across studies. We aim to develop a harmonized protocol based on expert consensus and histological evidence. Methods: Our international working group, funded by the EU Joint Programme–Neurodegenerative Disease Research (JPND), is working toward the production of a reliable, validated, harmonized protocol for segmentation of medial temporal lobe regions. The working group uses a novel postmortem data set and online consensus procedures to ensure validity and facilitate adoption. Results: This progress report describes the initial results and milestones that we have achieved to date, including the development of a draft protocol and results from the initial reliability tests and consensus procedures. Discussion: A harmonized protocol will enable the standardization of segmentation methods across laboratories interested in medial temporal lobe research worldwide. Highlights: Harmonization of MRI‐based segmentation of medial temporal regions is needed. The Hippocampal Subfield Group includes >200 imaging and anatomy experts worldwide. Reliable and valid protocol based on specialized histology data set in development. A modified Delphi procedure is used to determine consensus on protocol rules. Final protocol will provide subfield delineation in hippocampal body, head, and tail.